A New Jelly Ascomycetous Genus Record for Turkish Mycobiota - Ilgaz Akata; Abdullah Kaya (Süleyman Demirel Üniversitesi Fen-Edebiyat Fakültesi Fen Dergisi, 2010)
Abstract: Leotia lubrica (Scop.) Pers. was reported from Yomra district of Trabzon (Turkey). It is the first member of the genus Leotia to be recorded from Turkey. Short description and the photographs of the species are provided and discussed briefly.